Properties of n-type SnO2 semiconductor prepared by spray ultrasonic technique for photovoltaic applications. (December 2015) - Bendjedidi, H.; Attaf, A.; Saidi, H.; Aida, M. S.; Semmari, S.; Bouhdjar, A.; Benkhetta, Y.
Abstract: Transparent conducting n-type SnO2 semiconductor films were fabricated by employing an inexpensive, simplified spray ultrasonic technique using an ultrasonic generator at deferent substrate temperatures (300, 350, 400, 450 and 500 °C). The structural studies reveal that the SnO2 films are polycrystalline at 350, 400, 450, 500 °C with preferential orientation along the (200) and (101) planes, and amorphous at 300 °C. The crystallite size of the films was found to be in the range of 20.9–72.2 nm. The optical transmittance in the visible range and the optical band gap are 80% and 3.9 eV respectively. The films thicknesses were varied between 466 and 1840 nm. The resistivity was found between 1.6 and 4 × 10 −2 Ω·cm. This simplified ultrasonic spray technique may be considered as a promising alternative to a conventional spray for the massive production of economic SnO2 films for solar cells, sensors and opto-electronic applications.